PEDAGOGICAL INNOVATION IN DEVELOPMENT OF NEW DIRECTION OF EDUCATION - Kozak, Liudmyla V. (Educological discourse, 2014)
This paper presents a theoretical and methodological analysis of the general principles of educational innovation; the importance of educational innovation in the development of a new direction of education–osvitology; defined object and purpose of educational innovation; stages of innovative educational process; demonstrated a positive impact on the formation of pedagogical innovation ability of teachers to innovative profession.